A causal relationship between rheumatoid arthritis and bronchiectasis? A systematic review and meta-analysis. (12th February 2021) - Wiater, Rafal; Håkansson, Kjell Erik Julius; Ulrik, Charlotte Suppli
Rheumatoid arthritis (RA) is a chronic autoimmune disease primarily affecting joints but often also associated with lung involvement such as bronchiectasis (BE). The aim of the present systematic review and meta-analysis is to provide an update on the current evidence regarding the prevalence and association between RA and BE. This systematic review and meta-analysis was performed in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines with literature search using the terms 'Bronchiectasis AND Rheumatoid Arthritis' without a date limitation on PubMed during May 2020. A total of 28 studies fulfilled the predefined criteria and were included in the present review, with 19 being cross-sectional studies. Twenty-three studies were included in the meta-analysis. The pooled prevalence estimate was 2.69% (95% CI 1.63–4.42) in clinically defined BE, and 24.9% (95% CI 19.21–31.67) in radiologic disease. Many inconsistencies exist regarding potential risk factors for BE in RA patients such as gender, RA duration and severity, as both negative and positive associations have been reported. Although very little is known about possible causative mechanisms between RA and BE, potential pathways might be antigenic stimulation from pulmonary mucus and/or systemic inflammation from joint disease affecting the lungs. At present, the available evidence of bronchiectasis in patients with RA is insufficient to identify RA-associated risk factors for the development of BE, possibly apart from duration of RA, and, consequently, also to fully explore a possible causal relationship between the two disease. However, the increased prevalence of BE in RA patients warrants further studies to explore the association between RA and BE.